Cancer therapies in HIV cure research. Issue 1 (January 2017) - Rasmussen, Thomas A.; Anderson, Jenny L.; Wightman, Fiona; Lewin, Sharon R.
Abstract : Purpose of review: This article provides an overview of anticancer therapies in various stages of clinical development as potential interventions to target HIV persistence. Recent findings: Epigenetic drugs developed for cancer have been investigated in vitro, ex vivo and in clinical trials as interventions aimed at reversing HIV latency and depleting the amount of virus that persists on antiretroviral therapy. Treatment with histone deacetylase inhibitors induced HIV expression in patients on antiretroviral therapy but did not reduce the frequency of infected cells. Other interventions that may accelerate the decay of latently infected cells, in the presence or absence of latency-reversing therapy, are now being explored. These include apoptosis-promoting agents, nonhistone deacetylase inhibitor compounds to reverse HIV latency and immunotherapy interventions to enhance antiviral immunity such as immune checkpoint inhibitors and Toll-like receptor agonists. Summary: A curative strategy in HIV will likely need to both reduce the amount of virus that persists on antiretroviral therapy and improve anti-HIV immune surveillance. Although we continue to explore advances in the field of oncology including cancer immunotherapy, there are major differences in the risk–benefit assessment between HIV-infected individuals and patients with malignancies. Drug development specifically targeting HIV persistence will be the key to developing effective interventions with an appropriate safety profile.